6-Arylimino-2-(2-(1-phenylethyl)naphthalen-1-yl)-iminopyridylmetal (Fe and Co) Complexes as Highly Active Precatalysts for Ethylene Polymerization: Influence of Metal and/or Substituents on the Active, Thermostable Performance of Their Complexes and Resultant Polyethylenes - Wenhua Lin; Liping Zhang; Jiahao Gao; Qiuyue Zhang; Yanping Ma; Hua Liu; Wen-Hua Sun (Molecules, 2020)
A series of 6-arylimino-2-(2-(1-phenylethyl)naphthalen-1-yl)iminopyridines and their iron(II) and cobalt(II) complexes (Fe1–Fe5, Co1–Co5) were synthesized and routinely characterized as were Co3 and Co5 complexes, studied by single crystal X-ray crystallography, which individually displayed a distorted square pyramidal or trigonal bipyramid around a cobalt center. Upon treatment with either methyluminoxane (MAO) or modified methyluminoxane (MMAO), all complexes displayed high activities regarding ethylene polymerization even at an elevated temperature, enhancing the thermostability of the active species. In general, iron precatalysts showed higher activities than their cobalt analogs; for example, 10.9 × 106 g(PE) mol−1 (Co) h−1 by Co4 and 17.0 × 106 g(PE) mol−1 (Fe) h−1 by Fe4. Bulkier substituents are favored for increasing the molecular weights of the resultant polyethylenes, such as 25.6 kg mol−1 obtained by Co3 and 297 kg mol−1 obtained by Fe3. A narrow polydispersity of polyethylenes was observed by iron precatalysts activated by MMAO, indicating a single-site active species formed.